Prevalence of Malnutrition and Associated Factors among Under-Five Children in Pastoral Communities of Afar Regional State, Northeast Ethiopia: A Community-Based Cross-Sectional Study - Sedik, Yayo; Mulugeta, Afework; Reddy, P. Surender; Gebre, Abel; Kahssay, Molla (Journal of nutrition and metabolism, 2019)
Background. Malnutrition among children remains one of the most important causes of morbidity and mortality in the world. In Ethiopia, malnutrition is one of the most serious public health problem and the biggest in the world. This study aimed to assess the prevalence of malnutrition and associated factors among under-five children in pastoral communities of Afar Regional state, Northeast Ethiopia. Methods. A community-based cross-sectional study was conducted on 840 children aged 6–59 months from March 01–25, 2017. A multistage cluster sampling method was used to select the study participants. A structured questionnaire was used and anthropometric measurements were taken to collect data. EPI Data 3.1 and SPSS version 20.0 were used for data entry and analysis, respectively. Bivariate and multivariable logistic regression analysis was used to identify the factors associated with malnutrition. The statistical significance was declared at p value < 0.05 with 95% confidence intervals in the final model. Result. The study found the prevalence of wasting, stunting, and underweight was 16.2% (95% CI: 13.8–18.8%), 43.1% (95% CI: 39.8–46.5%), and 24.8% (95% CI: 21.9–27.8%), respectively. Family size (AOR = 2.72, 95% CI: 1.62–4.55), prelacteal feeding (AOR = 3.81, 95% CI: 1.79–5.42), and diarrhoea in the past two weeks (AOR = 4.57, 95% CI: 2.56–8.16) were associated with wasting. And sex of child (AOR = 1.98, 95% CI: 1.46–2.72), age of child ((12–23 months: AOR = 3.44, 95% CI: 2.24–5.29); (24–35 months: AOR = 3.58, 95% CI: 2.25–5.69); and (36–59 months: AOR = 4.42, 95% CI: 2.79–6.94)), and immunization status of child (AOR = 3.34, 95% CI: 1.31–4.81) were predictors for stunting. Moreover, mother’s education (AOR = 4.06, 95% CI: 2.01–8.19), sex of child (AOR = 1.83, 95% CI: 1.29–2.94), prelacteal feeding (AOR = 2.81, 95% CI: 1.64–3.72), and immunization status of child (AOR = 3.17, 95% CI: 2.14–4.99) were significantly associated with underweight. Conclusions. This study indicated that child malnutrition was high among under-five children. Family size of five and above, receiving prelacteal feeding, and diarrhoea in the past two weeks were positively associated with wasting. Male child, increasing age of child, and not fully immunized child were positive predictors for increasing stunting. Maternal illiteracy, male child, prelacteal feeding, and not fully immunized child were factors affecting underweight. Promoting use of family planning, preventing diarrhoeal diseases, and vaccinating children integrated with the access of nutrition education programs are vital interventions to improve nutritional status of the children.